2013
DOI: 10.1371/journal.pone.0056041
|View full text |Cite
|
Sign up to set email alerts
|

Sharing of Potential Nest Sites by Etheostoma olmstedi Males Suggests Mutual Tolerance in an Alloparental Species

Abstract: When reproductive competitors tolerate or cooperate with one another, they may gain particular benefits, such as collectively guarding resources or attracting mates. Shared resources may be those essential to reproduction, such as a breeding site or nest. Using the tessellated darter, a species where males but not females compete over potential nest sites, we examined site use and sharing under controlled conditions of differing competitor density. Sharing was observed even when competitor density was low and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Co‐breeding behaviors are often observed in some animal taxa, particularly in fishes. For example, males of darters (Percidae) and suckers (Catostomidae) share spawning grounds and display mutual tolerance for reproduction (Díaz‐Muñoz et al, 2014; Stiver et al, 2013). However, reproductive effort of those fishes is relatively less intensive than that of nest‐building species, who invest much more effort in nest construction by collecting nesting resources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Co‐breeding behaviors are often observed in some animal taxa, particularly in fishes. For example, males of darters (Percidae) and suckers (Catostomidae) share spawning grounds and display mutual tolerance for reproduction (Díaz‐Muñoz et al, 2014; Stiver et al, 2013). However, reproductive effort of those fishes is relatively less intensive than that of nest‐building species, who invest much more effort in nest construction by collecting nesting resources.…”
Section: Discussionmentioning
confidence: 99%
“…But in some species, males co‐breed with other males by building and sharing nests (Díaz‐Muñoz et al, 2014; Gross, 1996; Taborsky, 2009). This behavior is adaptive because males in a certain group may have a better chance to increase reproductive success (Balshine et al, 2001; Riehl, 2012; Sherley, 1990; Stiver et al, 2013; Theuerkauf et al, 2009). In addition, males of some species build multiple nests sequentially in a reproductive season (Friedl & Klump, 2000; Sumasgutner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that in a pond, adjacent nests with eggs were as close together as 10–20 cm. Sharing of a substrate by nesting males provides them with some benefits, such as less energetically expensive conflict, mutual defense of the site, and additive efforts to attract females (Stiver, Wolff, & Alonzo, ).…”
Section: Nestsmentioning
confidence: 99%
“…This behavior is adaptive because at least some males of a group bene t from increased reproductive success (Sherley 1990 leads to individual variation in reproductive success. But the social hierarchy is not readily evident in other species, where males lek or tolerate mutually on a nest (Taborsky 1994(Taborsky , 2009Stiver et al 2013;Díaz-Muñoz et al 2014). In these co-breeding species, the relationship between reproductive success and behavior is elusive.…”
Section: Introductionmentioning
confidence: 99%